MicroRNA-16 suppresses metastasis in an orthotopic, but not autochthonous, mouse model of soft tissue sarcoma - Mohit Sachdeva; Melody J. Whitley; Jeffrey K. Mito; Yan Ma; Dina C. Lev; Diana M. Cardona; David G. Kirsch (The Company of Biologists, 2015)
MicroRNAs (miRNAs) can regulate tumor cell invasion and metastasis in a tumor-specific manner. We recently demonstrated that global downregulation of miRNAs after deleting dicer can promote development of distant metastases in a mouse model of primary soft tissue sarcoma (STS). In this study, we identified miRNAs that are differentially downregulated in metastatic STS in both human and mouse, and investigated the role of these miRNAs in metastasis. miRNA- TaqMan PCR arrays showed a global downregulation of miRNAs in metastatic human sarcomas. Similar analysis in mouse metastatic sarcomas revealed overlap for several downregulated miRNAs including miR-16, miR-103, miR-146a, miR-223, miR-342 and miR-511. Restoration of these downregulated miRNAs in mouse primary sarcoma cell lines showed that miR-16, but not other downregulated miRNAs, was able to significantly suppress both migration and invasion in vitro, without altering cell proliferation. In addition, orthotopic transplantation of a sarcoma cell line stably expressing miR-16 into the muscle of immunocompromised mice revealed that restoration of miR-16 can significantly decrease lung metastasis in vivo. However, no change in the rate of lung metastasis was observed when miR-16 was deleted in mouse primary sarcomas at sarcoma initiation. Taken together, these results indicate that miR-16 can have metastasis-suppressing properties both in vitro and in vivo. However, the loss-of-function experiments in autochthonous tumors indicate that loss of miR-16 is not sufficient to promote metastasis in vivo.